Parents perspectives about their experience in the ACT-Raising Safe Kids program: A qualitative study - Ramos,Filipa (2019)
The present study aimed to explore Portuguese parents perspective about their experience and participation in the ACT-Raising Safe Kids Program (RSK), a universal parenting program to prevent child maltreatment. The sample consisted of 9 mothers and 1 father of 3 to 8 years old children who completed the ACT-RSK. Parental perspectives were assessed through a semi-structured face-to-face interview. Content analysis and descriptive statistic procedures were used to analyze the data. Findings indicate that parents chose to participate because they needed help to solve specific problems, wanted to improve parenting abilities and knowledge, and share experiences. As results of participating in the ACT-RSK, parents reported an increased awareness of parenting behaviors, an adjustment of expectations and acquisition of information. They also perceived increased emotional self-regulation, self-efficacy and use of positive parenting practices. These changes led to the enhancement of their childs self-regulation and awareness of rules, and a reduction in behavior problems. Regarding the implementation of the ACT-RSK, parents valued the contents addressed and belonging to a group. However, they identified personal and program barriers, including competing demands on parents time and considering some sessions less useful. Implications of these findings are discussed and future research questions are addressed.